Autism and the ghost of gender. (May 2016) - Davidson, Joyce; Tamas, Sophie
Abstract: The paper examines first-hand accounts of differently gendered emotional experience of the autism spectrum drawn from responses to online surveys, blogs and published autobiographies. Analysis of these materials reveals that atypical experiences and expressions of gender are considered relatively common among those on the spectrum. More literal minded than most, many describe meticulous attempts to seek out and solidify gender's troubling manifestations in their social worlds, only to find, of course, that no such thing as gender exists. However, this oddly absent presence continues to haunt autistic emotional lives; its uncanny leavings and doings persist, and most (neuro)typical others remain in its thrall, seeming to learn gender's nebulous rules as if telepathically. First-hand autistic accounts highlight the draining and relentless emotional labour that doing gender 'typically' requires, and many on the spectrum respond by explicitly rejecting or simply neglecting its confounding demands, identifying with neither side of the m/f divide in attempts to give up the ghost of gender.